Evaluating the use of Instagram images color histograms and hashtags sets for automatic image annotation - Giannoulakis, Stamatios; Tsapatsoulis, Nicolas; Djouvas, Constantinos (Frontiers in Big Data, 2023)
Color similarity has been a key feature for content-based image retrieval by contemporary search engines, such as Google. In this paper, we compare the visual content information of images, obtained through color histograms, with their corresponding hashtag sets in the case of Instagram posts. In previous studies, we had concluded that less than 25% of Instagram hashtags are related to the actual visual content of the image they accompany. Thus, the use of Instagram images' corresponding hashtags for Automatic Image Annotation is questionable. In this work, we are answering this question through the computational comparison of images' low-level characteristics with the semantic and syntactic information of their corresponding hashtags. The main conclusion of our study on 26 different subjects (concepts), is that color histograms and filtered hashtag sets, although related, should be better seen as a complementary source for image retrieval and Automatic Image Annotation.